(untitled) (Fiep Bulletin - online, 2024)
Introduction: Aging brings with it harmful effects such as: changes in body composition, increased blood pressure, development of metabolic diseases such as type 2 diabetes and changes in physical fitness variables. Such changes can compromise the functional capacity and limit the physical autonomy of the elderly, impacting their quality of life. Objective: To evaluate the effect of age on the relationship between muscular resistance and gait speed performance in physically active elderly women. Methods: Participants responded to a social anamnesis in an interview format with questions about personal health background, lifestyle and socioeconomic conditions. If the blood pressure is lowered, the weight and height are lower. Participants were familiarized with the functional tests: i) return and return test (2.44 m); ii) flexion of the code in 30 seconds; iii) get up and sit down from the chair in 30 seconds. Results: A weak negative correlation (r = -0.388; p = 0.006) was observed between the number of repetitions in the 30-second elbow flexion test and the Go and Come test. The correlation between the 30-second stand-up and sit-down test and the 30-second elbow flexion test showed a strong positive correlation (r = 0.685; p < 0.001). Age showed a weak positive correlation (r = 0.281; p = 0.048) with the gait speed test. Conclusion: Our study showed that advancing age in elderly women over 60 years old impacts on muscular resistance and consequently on gait performance.